The Paradox of Question and Answer Episode of Thesis Examination - Suprihadi Suprihadi (TEFLIN, 2004)
The main concern of this research is the exploration of tendencies made by the participants of a thesis examination in enacting their roles through their speech function choices. Interpretation of the data is based on the principle of critical discourse analysis within the systemic functional linguistic. The results show us the paradox of a Question Ã¢â¬â and Ã¢â¬â Answer episode of a thesis examination. It lies in the fact that it must operate in an academic atmosphere, be brief and frightening, and the examiners initiate the interaction by demanding information from the student, and yet it is a joint production of conversation in which, while enacting their supportive roles, the examiners contribute to sustaining the interaction, making it half-way between casual and pragmatic conversation. Based on the findings: some suggestions addressed to examiners are made.